A combined experimental and numerical approach to predict ship resistance and power demand in broken ice - Xue, Yanzhuo; Zhong, Kai; Ni, Bao-Yu; Li, Zhiyuan; Bergstrom, Martin; Ringsberg, Jonas W.; Huang, Luofeng (Elsevier, 2024)
Despite its remoteness and hostile environmental conditions, the Arctic holds significant shipping lanes, such as the Northern Sea Route (NSR) and the Northwest Passage (NWP). Typically, merchant ships operate along these routes in summer only, when the dominating type of ice is broken ice. A challenge of operating in such ice conditions is that there is no cost- and time-efficient method for predicting the resulting ice resistance, which makes route planning difficult, among others. To address this challenge, we present and analyze two complementary approaches to predict ship resistance in broken ice, of which one is experimental and the other numerical. The experimental approach makes use of a type of non-refrigerated synthetic model ice made of polypropylene, which makes it possible to test how a ship behaves in broken ice using a conventional non-refrigerated towing tank rather than an ice tank. The numerical approach, in turn, is based on the CFD-DEM method and can be used to consider fluid effects, such as the changes in fluid velocity and ship waves, while the ship is moving ahead. Validation calculations against established empirical approaches indicate that both approaches are reasonably accurate.
Keywords: Ship resistance; Broken ice; Coupled CFD-DEM approach; Model test; Non-refrigerated ice; Emperical formula